The Black charter, Political Expression of Gabriel Garcia Moreno’s Conservativeness - Ramírez Pinargote, Johanna Griselda; Troya Chasi, Jaime Alfredo; Coello Almagro, Maribel Jessenia; Borja Ramos, Oswaldo Rafael (RECIMUNDO, 2022)
This essay deals with one of the most controversial characters in Ecuadorian history, President Gabriel García Moreno, an Ecuadorian politics figure of the second half of the nineteenth century. Because of his actions during his presidential term, popular perception was divided, with some considering him an angel while others considering him a demon; in his second presidential term he convoked a National Convention to draft a new Magna Carta. The Constitution of 1869 was called the Black Charter by its contemporaries, by violating rights such as freedom of worship, freedom of expression; it was exclusionary because it did not allow the political participation of the vast majority of the population; education is based eminently on Catholic dogmas, despite all this, it was approved by referendum on July 18, 1869, by 96.36% of voters.